2014
DOI: 10.2196/jmir.3154
|View full text |Cite
|
Sign up to set email alerts
|

Movement-Based Interaction Applied to Physical Rehabilitation Therapies

Abstract: BackgroundHealth care environments are continuously improving conditions, especially regarding the use of current technology. In the field of rehabilitation, the use of video games and related technology has helped to develop new rehabilitation procedures. Patients are able to work on their disabilities through new processes that are more motivating and entertaining. However, these patients are required to leave their home environment to complete their rehabilitation programs.ObjectiveThe focus of our research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Technology that links virtual groups may overcome the potential barrier of social isolation and may be of benefit for both improving physical activity within a virtual social network for those people unable to mobilize easily outside the home. In the future, home-based preventive health care using technology may be leveraged off current research exploring in-home rehabilitation using motion capture software and technology [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Technology that links virtual groups may overcome the potential barrier of social isolation and may be of benefit for both improving physical activity within a virtual social network for those people unable to mobilize easily outside the home. In the future, home-based preventive health care using technology may be leveraged off current research exploring in-home rehabilitation using motion capture software and technology [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown, however, that supported discharge combined with at home rehabilitation services does not compromise clinical inpatient outcomes [ 5 - 7 ] and may enhance recovery in subacute stroke patients [ 8 ]. Hence, it is essential that new approaches are deployed that help to manage chronic conditions associated with stroke, including domiciliary interventions [ 9 ] and the augmentation of current rehabilitation approaches in order to enhance their efficiency. There should be increased provision of home-based rehabilitation services for community-based adults following stroke, taking cost-effectiveness, and a quick family and social reintegration into account [ 10 ].…”
Section: Introductionmentioning
confidence: 99%